Business Practices Linked to the Sustainable Development Goals (Docentes 2.0 Journal, 2026)
The Sustainable Development Goals (SDGs) constitute an ambitious agenda designed to address the world's most pressing challenges over a fifteen-year period. The objective of this research was to determine whether the largest companies in Mexico, by sales volume, actively contribute to achieving the Sustainable Development Goals (SDGs), and to examine the importance they place on non-financial information and on the promotion of Corporate Social Responsibility (CSR). To achieve this, research was conducted within the humanistic-interpretive paradigm, using the hermeneutic method, a qualitative approach, and a descriptive-interpretive, cross-sectional design. The research was based on non-financial information published by the twenty largest companies in each sales sector. Subsequently, data collection was systematized using Atlas. TI software to create maps. The results indicate that there is no uniformity in the criteria for rigorously assessing the scope of the SDGs. Furthermore, the companies analyzed do not take action to achieve all the SDGs, and they have a preponderance of activities to meet the goals of affordable and clean energy and clean water. In particular, there are no comparative standards in Mexico for companies' compliance with the 2030 Agenda; therefore, it would be important to conduct comparative studies with companies in other countries.
Keywords: Business practices; sustainable development; corporate social responsibility; corporate sustainability reports